PENGARUH FINANCIAL STABILITY, FINANCIAL TARGET, INEFFECTIVE MONITORING DAN PERGANTIAN AUDITOR TERHADAP FINANCIAL STATEMENT FRAUD: FINANCIAL STATEMENT FRAUD - Cucu Nurul Khotimah; Yunita Kurnia Shanti (Yayasan Kayyis Mulia Jaya, 2026)
This study aims to obtain empirical evidence regarding the effect of financial stability, financial target, ineffective monitoring, and auditor switching on financial statement fraud. The population of this study consisted of 38 healthcare companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. Using the purposive sampling method, 10 companies were selected as the research sample, resulting in a total of 50 observations. Financial stability was proxied by ACHANGE, financial target by Return on Assets (ROA), ineffective monitoring by the proportion of independent commissioners (BDOUT), and auditor switching by a dummy variable, while financial statement fraud was measured using the Modified Jones Model. The data were analyzed using panel data regression with the Random Effect Model (REM) through EViews 12. The results indicate that, partially, financial target has a significant effect on financial statement fraud, whereas financial stability, ineffective monitoring, and auditor switching have no significant effect. Simultaneously, the four independent variables have a significant effect on financial statement fraud. Keywords: Financial Statement Fraud, Financial Stability, Financial Target, Ineffective Monitoring, Auditor Switching